2014
DOI: 10.1016/j.apcata.2014.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Formation of active sites and hydrodesulfurization activity of rhodium phosphide catalyst: Effect of reduction temperature and phosphorus loading

Abstract: The Rh-1.5P catalyst exhibited the highest activity among the investigated catalysts. ► Rh2P was easily formed in catalysts with a higher P loading. ► Higher P loadings and higher reduction temperatures led to aggregation of Rh species. ► RhP2 exhibits lower catalytic activity than Rh2P. ► High HDS activity was caused by small Rh2P formation at lower reduction temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 41 publications
(68 reference statements)
7
60
0
Order By: Relevance
“…The main HDS products of the Rh _ P/NaMFI catalyst were butanes, butenes, tetrahydrothiophene (THT) and cracking products (C1-C3). This trend was similar with the HDS products of Rh _ P/SiO2 catalyst 13) at the same thiophene conversion (10.4 %). On the other hand, trace amount of 1,3-butadiene was produced over the Rh _ P/NaMFI and Rh _ P/NaBEA catalysts, and trace amount of 2-methylthiophene was produced over the Rh _ P/NaBEA catalyst.…”
Section: Thiophene Hds Conversionsupporting
confidence: 71%
See 2 more Smart Citations
“…The main HDS products of the Rh _ P/NaMFI catalyst were butanes, butenes, tetrahydrothiophene (THT) and cracking products (C1-C3). This trend was similar with the HDS products of Rh _ P/SiO2 catalyst 13) at the same thiophene conversion (10.4 %). On the other hand, trace amount of 1,3-butadiene was produced over the Rh _ P/NaMFI and Rh _ P/NaBEA catalysts, and trace amount of 2-methylthiophene was produced over the Rh _ P/NaBEA catalyst.…”
Section: Thiophene Hds Conversionsupporting
confidence: 71%
“…Therefore, the phosphates easily formed enlarged particles on the external surface. Reduction of large phosphate particles was facilitated because of the weak interaction between the phosphates and the support 13) . On the basis of these results, the maximum peak of phosphate reduction in the Rh _ P/NaMOR catalyst was observed at the lowest temperature among the Rh _ P/zeolite catalysts.…”
Section: Rh Species After Calcinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanda et al [6,29] applied the incipient wetness impregnation method for the preparation of Ru 2 P, PtP 2 , Rh 2 P, and Pd 4.8 P on SiO 2 to test the metal phosphides as catalysts in the HDS of thiophen. On later publications, Kanda et al [30] focused on the preparation of Rh 2 P on different support materials (SiO 2 , TiO 2 , Al 2 O 3 , MgO, and ZrO 2 ) and the effect of the reduction temperature and the effect of phosphorus loading [31] on the formation of Rh 2 P. The compound Rh 2 P can be successfully prepared on all the support materials investigated. Further, Kanda observed the formation of Rh 2 P on SiO 2 at lower reduction temperatures (350 • C) with a high excess of phosphorus (P:Rh = 2), while higher temperatures are required (550 • C) to form phase-pure Rh 2 P on SiO 2 samples with a lower excess of phosphorus (P:Rh = 1).…”
Section: Synthetic Pathways To Supported Platinum Group Metal Phosphidesmentioning
confidence: 99%
“…Further investigations have shown that Rh 2 P has a higher activity in the HDS of thiophene than all the other PGM phosphides [29]. Due to the higher intrinsic activity of the Rh 2 P catalyst, different publications have focused on the application of Rh 2 P as a catalyst material for hydrotreating reactions [27][28][29][30][31][32][33][34]43,47,52], for the hydrogen evolution reaction [53], and for the hydroformylation [35]. Reviews focusing on the metal phosphides in general and their applications as catalyst materials can be found elsewhere [24][25][26]49,54,55].…”
Section: Rh 2 P As a Prototypic Example For Pgm Phosphides In Hydrotrmentioning
confidence: 99%